The Effect of Voltage Changes Toward Time and Temperature Charging of Electrical Vehicle Battery - Andi Muhammad Nur Putra; Sitti Amalia; Sitti Amalia (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2023)
Technology in electric vehicles (EVs) has emerged as a major topic in the development of environmentally friendly and efficient energy. The battery is one of the most important components of an EV. Using the CCCV charging method, the battery will be more stable when charging. The performance of an EV mainly depends on its battery charging strategy. Consumers want fast charging with long-distance travel and good acceleration. Various filling techniques are currently in use, but research is still ongoing to find which one is more optimal and reliable. Modelling and simulation are very important to find out how to get optimal charging current or voltage, as well as determine the pattern of the charging circuit to shorten the charging time for EVs. This paper proposes a design and method that is carried out by changing the output voltage with a boost converter circuit to see the effect of time and temperature during charging and the simulation results are obtained regarding the length of time for charging Lithium-ion batteries. With the 420 V input voltage and 153 A, the battery is fully charged for 4500 seconds with a maximum temperature of 38° at a voltage of 420 V and the fastest charging time is 1200 seconds at an output voltage of 450 V with a maximum temperature of 62°. A 10 V voltage change resulted in a temperature increase of 6°C and a charging time of 600 seconds for each cycle.